EKSPLORASI KETERAMPILAN PENGELOLAAN KELAS DALAM MENUMBUHKAN SIKAP DISIPLIN SISWA DI SDN PASIRJATI - Amanda Tiara Natasya; Utomo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The background to this research is based on the importance of classroom management skills for a teacher in creating a constructive, safe and entertaining learning environment, which can improve student discipline. This research aims to describe the classroom management skills applied by teachers in fostering discipline in grade 3 students at SDN Pasirjati and to describe what obstacles are experienced by teachers in implementing good classroom management to foster student discipline in grade 3 SDN Pasirjati. This research uses a qualitative approach with a descriptive research design. The qualitative data analysis technique used is based on Miles and Huberman's interactive model, which includes three main steps: data reduction, data presentation, and conclusion or verification. Based on the results of research conducted in class 3 at SDN Pasirjati, it can be concluded that the classroom management skills carried out by teachers are in accordance with the indicators of success in classroom management skills which can foster students' disciplinary attitudes. Then, the obstacles experienced by teachers in implementing classroom management in class 3 at SDN Pasirjati are differences in character between students, family environmental factors, and finally facilities and infrastructure that are still inadequate.